INTEGRATED REPORTING: CHRONOLOGICAL LITERAURE REVIEW (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Integrated reporting is a relatively new category that has been actively studied over the last decade. The study ofpublishing activity on integrated reporting allows to form general trends in the thematic focus of existing publications,in particular, in their chronological presentation. The article reviews the scientific literature on integrated reportingbased on the analysis of the most cited publications from the Scopus, Web of Science and Google Scholar databases.Analysis of the bibliometric landscape of publications on integrated reporting involves the study of publishingactivity in terms of the most cited authors and publications on selected topics, determining the chronological specificsof publications on selected topics by keywords.For this purpose, publications were sorted by Scopus, Web of Science and Google Scholar databases by keywords“integrated reporting” with their use in publications in article titles, abstracts, and keywords. Through the in-builtbibliographic analysis tools of the Scopus and Web of Science databases, as well as the Publish or Perish software (forthe Google Scholar database), these publications were imported for further bibliometric analysis using VOSviewer.Systematization of thematic orientation of publications on integrated reporting by keywords, in particular theirchronological analysis is implemented by clustering using VOSviewer software by building a bibliometric map of thepublication based on Scopus and Web of Science databases.The results of the analysis show that integrated reporting is a relatively new scientific category that has beenactively studied for the last ten years. The chronological representation of the bibliometric landscape of publications inrecent years shows that the most relevant are studies in the field of integrated reporting, related to the study of itsquality; connection with the Sustainable Development Goals; formation of the value of the firm, etc.
Keywords: : integrated reporting, non-financial reporting, sustainability reporting, literature review, bibliometric analysis